Predictors of self-reported practice in ventilator-associated pneumonia (VAP) prevention among critical care nurses in Sarawak public hospitals - Jia Hui Tan; Chong Chin Che; Li Yoong Tang; Mei Chan Chong (PLoS ONE, 2025)
Background and objective Ventilator-associated pneumonia (VAP), a leading cause of ICU mortality, remains prevalent in Southeast Asia, with limited data on critical care nurses’ knowledge and prevention practices in Malaysia. The purpose of this study was to assess knowledge, self-reported practices, barriers, and predictors of VAP prevention among critical care nurses in Sarawak, Malaysia. Methods This cross-sectional study was conducted from July to August 2023 at four public hospitals in Sarawak, Malaysia. Universal sampling was used to recruit nurses from various critical care units managing patients requiring ventilator support. A self-administered questionnaire, consisting of four sections, was employed to gather background information from nurses, assess their knowledge, self-reported practices, and identify barriers related to VAP prevention. Results A total of 298 critical care nurses participated in the study. Of these, 66.8% demonstrated poor knowledge of ventilator-associated pneumonia (VAP) prevention; however, self-reported practices with VAP prevention were significantly high at 76.5%. A Pearson’s correlation test revealed a significant association between the nurses’ knowledge and their self-reported practices related to VAP prevention (p < 0.001). Additionally, multiple regression analyses identified several significant predictors of critical care nurses’ self-reported practices in VAP prevention, including their level of knowledge, type of unit, number of official beds, and sociodemographic factors (p < 0.05). While knowledge positively influenced self-reported practices, its impact was relatively minor compared to sociodemographic factors. Barriers to VAP prevention included nursing staff shortages, forgetfulness, and lack of written protocols. Conclusions The prevention of ventilator-associated pneumonia (VAP) is a multidisciplinary challenge, emphasizing the crucial role of critical care nurses. The findings from this study underscore the necessity for updated, evidence-based interventions that target knowledge gaps, self-reported practices, and barriers to effective VAP prevention.